Tumor Response End Points as Surrogates for Overall Survival in Immune Checkpoint Inhibitor Trials: A Systematic Review and Meta-Analysis. (15th July 2021) - Kok, Peey-Sei; Yoon, Won-Hee; Lord, Sally; Marschner, Ian; Friedlander, Michael; Lee, Chee Khoon
Abstract : PURPOSE: Many immune checkpoint inhibitors (ICIs) have been approved on the basis of tumor response end points in nonrandomized trials, including objective response rate (ORR) and duration and depth of response. We aimed to assess the validity of these end points as surrogate end points for overall survival (OS) in patients with advanced solid tumors treated with ICIs at trial and treatment arm levels. METHODS: ICI trials in advanced solid cancers published between January 1, 2000, and March 31, 2020, were included. Correlations between ORR, durable response (DR) of ≥ 6 months, complete response (CR), and OS were assessed for treatment comparisons (trial-level) and for patients receiving ICI (arm-level), using weighted linear regression. RESULTS: Sixty-three trials were eligible, including 58 randomized controlled trials and 20 nonrandomized controlled trials (78 ICI arms and 30, 815 patients). The majority were phase III (63%), and OS was the most common primary end point (40%). In relative treatment comparisons, correlations between ORR risk ratio and OS hazard ratio (HR), 6-month DR ratio and OS HR, and CR ratio and OS HR were r = 0.58, r = 0.62, and r = 0.42, respectively. Exploratory studies in melanoma, non–small-cell lung cancer, and other tumors showed similar results, although 6-month DR ratio was strongly correlated with OS HR ( r = 0.89). Within ICI arms only, correlations between ORR and 12-month OS, 6-month DR and 12-month OS, and CR and 12-month OS were r = 0.76, r = 0.84, and r = 0.50, respectively, in all eligible trials. CONCLUSION: Relative measures of tumor response (ORR, 6-month DR, and CR) are poor surrogate end points for OS in ICI studies. However, ORR and 6-month DR are prognostic of 12-month OS in ICI studies supporting their use for screening activity of novel agents in early-phase nonrandomized trials.